2014
DOI: 10.1155/2014/958291
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Diuretic Activity and Calcium‐Sparing Effect of Tropaeolum majus: Evidence in the Prevention of Osteoporosis

Abstract: Although several studies indicate high effectiveness in the use of the hydroethanolic extract from Tropaeolum majus (HETM) as a diuretic, the impact of its prolonged use in the presence of low estrogen levels remains unclear. Thus, the aim of this study was to investigate the diuretic effects of prolonged administration of HETM in ovariectomized rats and their interrelationship between calcium excretion and bone turnover. Forty-two female Wistar rats were ovariectomized (OVX) and treated orally with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Since the main role of OC is bone mineralization, the body's calcium levels can profoundly alter its production and homeostasis. Calcium metabolism is very important during postmenopausal osteoporosis, the close relationship between reduced estrogen levels and bone loss may be directly related to this ion [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the main role of OC is bone mineralization, the body's calcium levels can profoundly alter its production and homeostasis. Calcium metabolism is very important during postmenopausal osteoporosis, the close relationship between reduced estrogen levels and bone loss may be directly related to this ion [11].…”
Section: Discussionmentioning
confidence: 99%
“…Osteocalcin, is a protein that plays an important role in bone mineralization, originates from osteoblastic synthesis and is deposited in the bone or released into the circulation, where it correlates with histological measures of bone formation [10]. In addition, osteocalcin can activate monocyte differentiation, resulting in an increase in the number of active bone resorption cells and promoting osteoclastic differentiation [11].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also demonstrated that the ethanolic extract increased diuresis similarly to spironolactone, a conventional K + -sparing diuretic, an effect that they associated with decreased plasmatic aldosterone levels [20]. Extending the studies on this plant, Barboza et al [21] evaluated the effect of hydroethanolic extract of T. majus leaves at doses of 3, 30, and 300 mg/kg in ovariectomized rats over a 4-wk period to determine whether long-term treatment with the extract would impact on the presence of low levels of estrogen. The results of that study demonstrated that T. majus extract was able to sustain its diuretic effect after 4 wk of treatment and did not affect the urinary excretion of Ca 2+ and K + , confirming the potential of the extract as a candidate for use in clinical conditions such as osteoporosis, in which renal loss of Ca 2+ is not desired.…”
Section: Brazilian Medicinal Plants With Diuretic Potentialmentioning
confidence: 91%
“…Estudos farmacológicos demonstraram atividades anti-hipertensiva (GASPAROTTO JUNIOR et al, 2011), anti-inflamatória (LOURENÇO et al, 2011), diurética (GAS-PAROTTO JUNIOR et al, 2009), na prevenção da perda de massa óssea, devido a preservação de osteocalcina e cálcio (BARBOZA et al, 2014), no tratamento de asma, constipação (LORENZI; MATOS, 2002;BOORHEM et al, 1999;PANIZZA, 1998), também utilizada como antibacteriana e antifúngica (ZANETTI et al, 2003;PANIZZA, 1998;LO-ZENZI;MATOS, 2002).…”
Section: Desenvolvimentounclassified